A deeper understanding of the relationships between 'firm size' and supply chain digitalisation: an empirical investigation. (29th November 2022) - Ruel, Salomée; Viale, Laurence; Zouari, Dorsaf
In a context of unprecedented crises and uncertainties, digital tools appear to bring more visibility to decision-takers along the supply chain (SC). They enhance information sharing and collaboration between SC entities. This research contributes to providing a more complete understanding of the relationships between the size of the firm and its adoption of SC digital tools and the challenges encountered. For this purpose, we mobilise the resource-based view (RBV) and analyse 311 surveys collected from SC professionals using the Kruskal-Wallis and Mann-Whitney tests. Our results clarify the role of firm size in SC digitalisation. More precisely, groups of different firm sizes show a significant difference of SC digital tools adoption level and our study enables researchers and practitioners to understand that this difference depends on the type of tools (either operational or support tools). In addition, this study brings a counter-intuitive result that is not consistent with previous research: there is no difference between the groups of different firm sizes with regards to SC digitalisation challenges encountered.